The effect of fiber reinforcement on the high-temperature performance of warm mix asphalt produced using water-foaming technology - Chomicz-Kowalska, Anna; Janus, Karolina (International Conference “Environmental Engineering”, 2026)
The paper presents an evaluation of the influence of fiber type and content on the properties of mineral-asphalt mixtures produced using foamed bitumen technology. The effects of selected factors, including the type of asphalt binder, the type of fibers, and their content, on the high-temperature performance of AC 11 asphalt concrete mixtures intended for wearing courses were analyzed. Aramid fibers and polymer-basalt fibers, applied in varying amounts, were used as dispersed reinforcement. The study also included a reference mixture produced and compacted using conventional Hot-Mix Asphalt (HMA) technology. In contrast, Warm-Mix Asphalt (WMA) mixtures with foamed bitumen were manufactured at a temperature reduced by 30 °C compared to the reference mixture. The evaluated basic properties of the asphalt mixtures included air void content and moisture sensitivity, determined using the indirect tensile strength ratio after one freeze-thaw cycle. High-temperature performance was assessed based on resistance to rutting, expressed by the wheel tracking slope and proportional rut depth, as well as the stiffness modulus determined by the static creep test. The obtained results indicate that reducing the production temperature of asphalt concrete mixtures by 30 °C is feasible through the application of dispersed fiber reinforcement while maintaining performance parameters comparable to those of the reference HMA mixture.
Keywords: asphalt concrete; Warm Mix Asphalt (WMA); dispersed reinforcement; fibers; high-temperature performance